Analysis Of Business To Business E-Commerce (International Journal of Scientific Research and Management (IJSRM), 2018)
Electronic business is more than just another way to enhance the business practices. B2B e-commerce is paradigm shift influencing both the buyer and supplier. E-business showing tremendous business growth in our country. The massive increase in digital technology has added growth of business and differentiating business model. this study describes the present scenario of electronic business, describe the business portal and analysis the changing trends. The study further examines the strength and weakness of business to business e-commerce and analysis the opportunity and threat of e-business.